Strengthening citizenship education in secondary school: a service- learning proposal - Ángela María Figueroa Iberico (Pontificia Universidad Católica del Perú, 2013)
To form people that develop in an active and compromised way their citizenship to solve community and country problems is the objective of our present education. However some specialists observe mistakes in our civic education noticing that it needs an integral and structural change. School is the perfect place to constantly practice citizenship through the practice of values, capacities and abilities that allow students interact among them, with their authorities and with society members. In this article, it presents a service-learning proposal which links learning and solidarity service in order to apply the acquired knowledge in the classroom for community service developing competences in daily contexts.